PEDAMPINGAN PEMANFAATAN DIGITAL MARKETING MELALUI GOOGLE BUSINESS PADA UMKM KELURAHAN KERTAJAYA - MAULA, JEANNITA ARIYEL (Education and Talent Development Center of Indonesia, 2022)
One of the problems faced by MSMEs in Kertajaya Village is the lack of knowledge about digital marketing technology. MSMEs in Kertajaya Village need technology-based business development so that they can compete with other online businesses. The method used in identifying the use of marketing media is by conducting (1) pre activities, filled with surveys and interviews (2) activities, filled with the delivery of material on the material presented (3) assistance filled with the practice of making Google Maps. The methods used in technology-based business development efforts are community education and training methods. The materials in technology-based business development in Kertajaya Village MSMEs are 1) marketing understanding, 2) digital marketing and branding, 3) digital marketing objectives, 4) utilization of Google Business as a means of digital marketing. Utilization of Google Business as a means of digital marketing. The results of the identification show that many MSMEs in Kertajaya Village still use conventional word-of-mouth marketing methods. There are still many MSMEs in Kertajaya Village that have not registered their shops on Google Maps. In addition, MSMEs in Kertajaya Village also do not have a logo for their products. The evaluation results of the digital marketing training and mentoring activities received a positive response because they were considered to provide insight, knowledge, and inspiration to MSME actors. It can also be seen that all business actors want to practice this online business to develop their business.